ESCO: Boosting Job Matching in Europe with Semantic Interoperability. - le Vrang, Martin; Papantoniou, Agis; Pauwels, Erika; Fannes, Pieter; Vandensteen, Dominique; De Smedt, Johan (Computer (00189162), 2014)
ESCO--the multilingual European Skills, Competences, Qualifications, and Occupations classification--lets stakeholders in the EU labor market better understand information they exchange. Such semantic interoperability will help address the chronic mismatch between unemployed workers' skills and companies' needs.